2011
DOI: 10.21608/ejabf.2011.2086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oil pollution on serum growth hormone (GH) levels,histology and Ultrastructure of muscles of the Nile Tilapia (Oreochromis niloticus)

Abstract: ABSTRACTver the last decades, there has been a growing interest in studying the main problems that could be harmful to the River Nile system in Egypt. Attention was paid to one of the most important problems that face the River Nile, this is called River Nile transport project. So the main objective of the present study was to investigate the adverse effects that can result from spilled gasoline as petroleum product from various motor ships into the River Nile on one of the most important popular fishes in Egy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In the muscle of D. rerio exposed to TMS, an increase in the intramyofibril space was observed, which can cause greater instability in the movement of the fish, increasing its vulnerability. Moreover, this alteration can culminate in cellular degeneration [ 69 ]. This finding raises concerns, as most vaccines are given intramuscularly.…”
Section: Discussionmentioning
confidence: 99%
“…In the muscle of D. rerio exposed to TMS, an increase in the intramyofibril space was observed, which can cause greater instability in the movement of the fish, increasing its vulnerability. Moreover, this alteration can culminate in cellular degeneration [ 69 ]. This finding raises concerns, as most vaccines are given intramuscularly.…”
Section: Discussionmentioning
confidence: 99%
“…Even though it is generally regarded as having a low potential for contaminating surface waters due to its perceived rapid dissipation and strong adsorption to soils and sediments, it has been detected in surface waters long after being used to kill aquatic weeds [34]. In fact, its mode of action was designed to affect only plants [29], but various studies in recent years have reported adverse impact on non-target animals [23,33,35]. These impacts could be lethal or sublethal.…”
Section: Effects Of Glyphosate-based Herbicides On Aquatic Animalsmentioning
confidence: 99%